Dampak Kebijakan Billing System Penebusan Pupuk Subsidi di Provinsi Lampung - Muhammad Ibnu (Jurnal Sosial Ekonomi Pertanian, 2021)
To address the problems of the distribution of subsidized fertilizers, the Government of Lampung Province implements an innovative Billing System policy through which farmer groups redeem subsidized fertilizer online. However, the impact of the policy has not been reviewed scientifically. Therefore, this study aims to answer questions (1) what are the impacts of the Billing System Policy on the quantity use and prices of subsidized fertilizer in Lampung? and (2) what are the impacts of the Billing System Policy on rice production in Lampung? The study was conducted in June 2020 until February 2021. Total respondents were 314 rice farmers surveyed with systematic random sampling in the districts of East dan South Lampung and Metro. The impacts of Billing Systems were evaluated with the Propensity Score Matching (PSM) technique, which is a credible quantitative method for correcting selection bias and other variable biases. The results showed that, at the farmer group level, the Billing System significantly increases the average use of Urea and reduces the average prices of Urea and SP36. However, the Billing System has little impact on rice production, although the production has increased after the Billing System policy. The findings further imply that enhancing the institutional capacity of farmers is still necessary.